Delivering effective training sessions - McArdle, Geri E.H. (Crisp Pub. Menlo ParkUS, 1993)
Seeks to teach the basic techniques of delivering profitable training presentations. Gives step by step guidance about organizing material during preparation; setting up the environment; using materials effectively; encouraging audience participation; and dealing with problems which may arise.